Análise da oxidação em matrizes de concreto refratário com adição de carbeto de silício - Eduardo José da Costa e Souza (2022)
The increase in competitiveness in the refractory castable industry has stimulated engineering studies in the search to improve the performance of these materials and reduce costs. Premature failures in refractory cause huge losses with repair costs, but mainly with the loss of production, failing to serve customers and comply with production planning. Carbon oxidation is one of the most complex failure mechanisms. An alternative explored to control the degradation of refractory castable is the addition of silicon carbide (SiC), which is recognized as an essential compound for resistance to high temperatures, good resistance to corrosion and thermal shock. In this context, the objective of this work is to study the influence of the addition of silicon carbides in refractory castable, understanding the mechanical and chemical behavior when exposed to an alkaline environment and high temperature. For this, concrete specimens were constructed without silicon carbide and with the addition of 10, 30 and 60% of SiC for analysis of its oxidation process comparing the results. These matrices were heated with different heating rates and residence time in the kiln. All samples were weighed before and after the kiln procedure, using x-ray diffraction and scanning electron microscopy techniques to understand the reactions. A lower rate of mass reduction of the matrix with 10% SiC was verified through these tests, which indicates greater resistance to oxidation, mainly associated with the formation of mullite Al6Si2O13 through the reaction between SiC and aluminum oxide Al2O3 present in the concrete composition, the presence of fly ash and the formation of a layer of silica SiO2 on the surface of the SiC, and this deposition acts as an antioxidant protector and, consequently, anticorrosion.